Effectiveness of Antagonistic Agents from Several Bacillus spp. Isolates against Anthracnose Disease (Colletotrichum capsici) in Chili Pepper Fruit (Capsicum annuum L.) - Nabiella, Aullyvia Putri; Wuryandari, Yenny; Nirwanto, Herry (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to evaluate the antagonistic activity of selected Bacillus spp. isolates against Colletotrichum capsici and determine the most effective isolate and cell density for suppressing anthracnose in red chili pepper. The study was conducted under in vitro and in vivo conditions. The in vitro assay tested five Bacillus spp. isolates, namely Bcz-14, Bcz-16, Bcz-20, Bcz-21, and Bcz-30, at cell densities of 10⁹ and 10¹⁰ CFU/mL. The three most effective treatments from the in vitro assay were subsequently evaluated under in vivo conditions. Data were analyzed using SPSS version 24 through analysis of variance (ANOVA) at a 5% significance level, followed by Tukey’s honestly significant difference (HSD) test at 5% when significant differences were detected. The results showed that B1K1 treatment (Bcz-14 at 10⁹ CFU/mL), with an inhibition zone of 5.83 mm; B5K1 treatment (Bcz-30 at 10⁹ CFU/mL), with an inhibition zone of 5.50 mm; and B2K1 treatment (Bcz-16 at 10⁹ CFU/mL), with an inhibition zone of 4.16 mm, exhibited the most stable inhibitory effects against C. capsici growth in vitro. The in vivo assay demonstrated that B1K1 treatment (Bcz-14 at 10⁹ CFU/mL) was the most effective treatment, resulting in a disease intensity of 26.25% and a control efficacy of 51.16%.